Improving Accounting Information at BUM Desa Mertha Buana Kayubihi Bangli - Wicaksana, Ketut Arya Bayu; Bagiada, I Made; Suarta, I Made; Suwintana, I Ketut; Handayani, Luh Nyoman Chandra (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2024)
BUM Desa Mertha Buana is a microfinance institution owned by the village government located on Jalan Nusantara Kayubihi, Bangli District, Bangli Regency. In its activities of producing accounting information, BUM Desa Mertha Buana uses a general journal and produces a statement of financial position and a profit and loss statement. The use of general journals to record repetitive transactions will cause the time spent doing clerical activities to be longer. The purpose of this community service is to help BUM Desa produce accounting information that is timely and in accordance with local government regulations using a worksheet-based cash receipts and disbursement special journal. The method used is science and technology substitution, accompanied by training for BUM Desa. After using the worksheet-based special cash receipts and disbursement journal, BUM Desa is able to produce financial reports as required by the Regional Government of Bangli Regency in a timely manner.